Kajian Literatur Faktor-Faktor yang Mempengaruhi Kepercayaan Konsumen terhadap Produk UMKM Berlabel Halal - Alnamira Alnamira; Nurul Karimah; Bahari Bahari; Fadhil Musyafa; Pani Akhiruddin Siregar (Politeknik Kampar, 2024)
This study aims to identify factors that influence consumer trust in halal-labeled micro, small, and medium enterprises (MSMEs) products. In Indonesia, the halal label plays an important role in purchasing decisions, especially among Muslim consumers who are looking for products that comply with Islamic law. This label not only guarantees the conformity of the product with Islamic law but also increases consumer trust in the safety and quality of the product. This study uses a literature study approach, analyzing various relevant references related to Islamic business management and consumer trust. The main factors identified include product quality, brand image, risk perception, and social influence. Consistent product quality, transparency in the production process, and a strong brand image contribute to increasing consumer trust and loyalty. In addition, social influence through recommendations from family and friends, as well as reviews on social media, play a significant role in shaping consumer perceptions. This study concludes that these factors are not only important for Muslim consumers but can also attract the interest of non-Muslim consumers who prioritize safety and ethics. This study provides insight for MSMEs in designing marketing strategies and product development, and is expected to support policies that encourage the growth of the halal MSME sector in the domestic and international markets.